Case Report: Acute Intracardiac Thrombosis in Children With Coronavirus Disease 2019 (COVID-19) - Hamid Bigdelian; Hamid Bigdelian; Mohsen Sedighi; Mohammad Reza Sabri; Bahar Dehghan; Chehreh Mahdavi; Alireza Ahmadi; Mehdi Ghaderian; Hamid Rahimi; Atefeh Sadeghizadeh; Monirsadat Emadoleslami; Seyed Nasser Mostafavi; et al. (Frontiers Media S.A., 2021)
We herein describe a case series of children with SARS-CoV-2 infection (COVID-19) complicated with acute intracardiac thrombosis. The diagnosis of COVID-19 was confirmed through the reverse transcription-polymerase chain reaction (RT-PCR). Transthoracic echocardiography of patients revealed large intracardiac mobile masses resected successfully via cardiac surgery. The underlying mechanisms of this thrombus in the COVID-19 infection may be attributed to the hypercoagulation and inflammatory state of the disease incurred by the SARS-CoV-2 virus.